Bimbingan Penerapan Media Flash Card dalam Meningkatkan Hafalan Doa-Doa Harian pada Pembelajaran PAI - Siti Lutfi Robi’atul Adawiyah; Solihah Bagus; Sobar Sanusi; Usep Setiawan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The process of learning daily prayer memorization is still largely carried out using conventional approaches, such as repeatedly reading from textbooks or delivering material through lecture-based methods. The researcher made efforts to improve students’ ability to memorize daily prayers in Islamic Religious Education learning through the use of flash card media in Cikeris Village. Through this activity, it is expected that flash card media will not only enhance students’ memorization skills but also create a learning atmosphere that is more engaging, enjoyable, and meaningful for learners. This study employed a descriptive qualitative approach using a community service method. The results of the study indicate that the use of flash card media in the Pojok Bahasa dan Literasi (Language and Literacy Corner) activities in Cikeris Village, RT 07, was effective in improving students’ ability to memorize daily prayers. This media helps students remember prayers more easily by combining elements of text, color, and images, thereby strengthening memory retention and increasing students’ self-confidence when reciting prayers. The use of flash cards also increased learning motivation and participation. Students became more active, enthusiastic, and interested in participating in the learning process because the method used was interactive and enjoyable.